A single-site randomized controlled trial of partner navigation to HCV treatment for people who inject drugs: a study protocol for the You’re Empowered for Treatment Initiation (YETI) partner trial - Meghan D. Morris; Judy Y. Tan; Claire C. McDonell; Maia Scarpetta; Tiffany N. Nguyen; Jennifer C. Price; Torsten B. Neilands (Trials)
Abstract Background Disparities persist in testing and treatment for hepatitis C virus (HCV), leaving socially marginalized populations, including people who inject drugs (PWID), less likely to benefit from curative treatment. Linkage services are often insufficient to overcome barriers to navigating the medical system and contextual factors. Methods The You’re Empowered for Treatment Initiation (YETI) Partner trial is a single-site randomized controlled trial evaluating the efficacy of a two-session behavioral intervention that engages injecting partners as peer navigators for HCV treatment. We aim to recruit 250 PWID and their primary injecting partners in San Francisco, California, randomizing them 1:1 to either a control or intervention group. The primary outcome is the initiation of HCV treatment, with secondary outcomes including treatment completion and sustained virologic response 12 weeks post-treatment. Data will be collected through questionnaires and electronic health records and analyzed using intention-to-treat and mixed-effects models. Discussion This trial will provide evidence of a new HCV treatment linkage intervention leveraging the support of primary injecting partners to initiate HCV treatment. If successful, the intervention could inform public health strategies and policies to address HCV in marginalized populations. Trial registration ClinicalTrials.gov NCT06179498. Registered on December 22, 2023.